Survei Aktivitas Fisik Dosen di Lingkungan Universitas Negeri Malang - Wahyono, Irellia Greavil; Widiawati, Prisca (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The purpose of the study was to eval_uate the level of physical activity of lecturers at the State University of Malang. The research method applied is descriptive with a quantitative approach in the form of numbers, using surveys as a data collection technique. The population in this study were lecturers from 8 faculties in the State University of Malang. The data collection technique in this study used purposive sampling technique. Purposive sampling is a sampling technique based on the consideration of the researcher or eval_uator about which samples are the most useful and representative or appropriate and representative according to (Retnawati,). The reason for using purposive sampling technique is because it is suitable for quantitative research, or studies that do not generalize. The criteria used in this study are men and women of productive age, namely 20-60 years old who are married. The samples taken in this study were 80 lecturers from 8 faculties at the State University of Malang. The results of METs measurement research with a total of 80 lecturers, high METs category as many as 31 lecturers with a percentage of 38.7%, moderate amounted to 44 lecturers with a percentage of 55.5%, and low amounted to 5 lecturers with a percentage of 6.3%. The conclusion of the research on the survey of physical activity of lecturers at the State University of Malang is that the results of the Metabolic Equivalent (MET) of 80 lecturers include 31 lecturers (38.8%) in the active category, 44 lecturers (55.5%) in the moderate physical activity category, and 5 lecturers (6.3%) in the low physical activity category.